Fatores-chave de sucesso na adoção de aplicativos móveis de táxi - Vasconcelos, Pattrisce Raymundo de (2014)
The research aims to investigate the key success factors in the adoption of mobile taxi applications (AMTs) by taxi drivers. Based on the Technology Acceptance model (DAVIS, BAGOZZI, WARSHAW, 1989), Diffusion of Innovation (ROGERS, 1995) and Trust (CARTER; BÉLANGER, 2005), the paper also proposes a review of the literature applied to the Mobile Application context of AMTs (VAN BILJON; Kotze, 2007). For the purpose of the research, the AMTs are defined as mobile service advanced applications which enable, through Internet and geolocation, a taxi transportation request in mobile devices, by means of information systems and phone calls, also monitoring the service provision and payment. Based on semi-structured interviews and questionnaires applications in field research, the study proposes a triangulation of the methods Lexical Analysis (BOTTA,2010; GEERAERTS,2010), Content Analysis (BARDIN, 2006), and Average Ranking (OLIVEIRA, 2005) for the investigation of the identified factors in the literature. The results indicate that the success factors influencing the adoption of AMTs by taxi drivers, are Simplicity and Perceived Usefulness, while moderators are Security and Financial Gains. It is believed that the research can contribute to the discussion of a topic still few explored in the literature in Brazil, Mobile Applications, and provide managerial implications for innovation in applications development companies.